Mining the Earth's Heat: Hot Dry Rock Geothermal Energy - Brown, Donald W.; Duchane, David V.; Heiken, Grant; Hriscu, Vivi Thomas; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
Mining the Earth's Heat: Hot Dry Rock Geothermal Energy describes the work carried out by the Los Alamos National Laboratory to turn an idealistic concept - that of drawing useful amounts of energy from the vast underground store of hot rock at reachable depths - into a practical reality. This book provides comprehensive documentation of the over two decades of experiments carried out at the test site at Fenton Hill, New Mexico, where the feasibility of accessing and extracting this vast natural resource was finally demonstrated. It also discusses the numerous technical, administrative, and financial hurdles that had to be overcome along the way. This publication will no doubt prove invaluable to researchers around the world as they strive to move this now-proven technology toward commercial viability. In addition, it is a valuable source of relevant information for anyone interested in the world energy outlook for the 21st century and beyond.
PART I Hot Dry Rock Geothermal Energy: History and Potential of the Newest and Largest Renewable Energy Resource -- PART II First Demonstration of the Hot Dry Rock Geothermal Energy -- Concept: Development of the Phase I Reservoir at Fenton Hill -- PART III Engineering the HDR System: Development and Testing of the Phase II Reservoir at Fenton Hill -- PART IV Future Outlook for Hot Dry Rock -- Appendix -- Glossary -- Bibliography -- Index.
Keywords: Geography; Geology; Earth Sciences; Geology